The impact of emotional dysregulation on food addiction: Examining the intervention role of gender - Jun Li; Lingjie Wang; Feng Xia; Ling Pan; Jia-Fu Liu (Acta Psychologica)
Food addiction (FA) is a significant barrier to the overall well-being of college students. Consequently, it is crucial to investigate the factors contributing to FA to address and alleviate the obesity issue among college students effectively. This study assessed the impact of emotional dysregulation (ED) on FA in a sample of 501 students at three universities in China and explored the gender disparities in this relationship. The results indicated a substantial positive association between ED and FA among college students. ED was found to be a significant and positive predictor of FA. Additionally, gender was found to moderate the influence of ED on FA. The results of this study offer a comprehensive empirical analysis to identify the factors contributing to FA in college students. Additionally, it provides recommendations for assisting college students in effectively managing their emotions, which in turn aids in accurately perceiving and successfully combating FA.